The Study of the Local Wisdom Existence in the Land System in Forest and Land Fire Control in Kurun District, Gunung Mas Regency - Berkat Berkat; A. Pisi (Budapest International Research and Critics University, 2020)
Farming practices for the people of Gunung Mas Regency are the oldest ancestral culture which is full of economic, social, cultural, religious and ecosystem wisdom values which are believed to still exist and are practiced in community farming activities. Learning from the experience carried out from generation to generation, in general the community indirectly has local knowledge (indigeneous knowledge) about good fire management. This research uses descriptive qualitative method with a case study approach. The results showed that various forms of local wisdom in farming activities, both in the form of rituals and traditions, still exist today, although in practice not all cultivators apply them. The application of various local wisdoms in farming practices to date is reflected in the behaviour of farmers in site selection, land clearing, slashing and logging, burning land and planting / planting activities. The implementation of local wisdom in farming activities is actually quite capable of playing a role in controlling forest and land fires. This can be seen from the small number of cases of forest and land fires caused by agricultural activities in Kurun District, Gunung Mas Regency.